Neuropsychological Testing in Mild Traumatic Brain Injury: What to Do When Baseline Testing Is Not Available. Issue 3 (September 2016) - Arnett, Peter; Meyer, Jessica; Merritt, Victoria; Guty, Erin
Abstract : Barth and colleagues' seminal study using baseline neuropsychological testing as a model for sports concussion management serves as the template for many collegiate sports medicine programs. However, there remains a significant need for an evidence-based strategy in cases where no baseline testing has been conducted. In this article, we further articulate such a model based on work with athletes at our Division I university. The foundation of the model involves base rates of impairment in a typical neurocognitive sports concussion battery, with decision rules that differ slightly for males and females. There is flexibility in the model such that its application can start during an acute period postconcussion when athletes are still potentially symptomatic, as well as after athletes self-report being symptom free. We use our population of collegiate athletes and the tests we administer as a framework to provide concrete values to the proposed algorithm based on specific tests, but the logic of our evidence-based model could easily be applied to other sports concussion populations and neurocognitive test batteries. Our proposed neuropsychological concussion management guidelines are evidence based, but also allow for accommodating trends in the literature which suggest that increasingly individualistic clinical concussion management approaches are most prudent.